If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 50 = 0 Reorder the terms: 50 + 2x = 0 Solving 50 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-50' to each side of the equation. 50 + -50 + 2x = 0 + -50 Combine like terms: 50 + -50 = 0 0 + 2x = 0 + -50 2x = 0 + -50 Combine like terms: 0 + -50 = -50 2x = -50 Divide each side by '2'. x = -25 Simplifying x = -25
| 81^3t+7=(1/27)^-2t+8 | | 12x+28=6x-24 | | 3x.x=10 | | X^2+4x=7x+18 | | -7.3q+1.4=28.6-1.3q | | 6a/8-2a/12+7/2=7 | | 2340=13 | | 3r+27=0 | | -m/4+5/-6=7-6 | | 2x/9=6 | | 2x/9+2=4 | | 27x+49=-167 | | 1/-2+y=2/3 | | M^2+2m+1/m^2-2m-3=7 | | 10/-6 | | M^2+2m+1/m^2-2m-3=0 | | 56=42+u/11 | | 12+d/9=27 | | 4y-192=96 | | 9/-3-2x=9 | | -9-5x=-31 | | 6x-5x=45 | | (x+1)/5 | | -77-5x=-31 | | x^2+x+0.2925636=0 | | 13.04+x=28.96 | | 6(2x-5)-11x=8 | | 29-3x=2x+4 | | 13.04+x^5=28.96 | | 29x-13=306 | | 10y-2=7+3G | | 3b^2-b-7=4b(2b+3)-1 |